Detection of gas hydrates in faults using azimuthal seismic velocity analysis,Vestnesa Ridge, W-Svalbard Margin - Singhroha, Sunny; Bünz, Stefan; Plaza Faverola, Andreia Aletia; Chand, Shyam (Journal of Geophysical Research: Solid Earth, 2020)
Joint analysis of electrical resistivity and seismic velocity data is primarily used todetect the presence of gas hydrate-filled faultsand fractures. In this study, we present a novel approach to inferthe occurrence of structurally-controlled gas hydrateaccumulations using azimuthal seismic velocity analysis. We perform thisanalysis using ocean-bottom seismic (OBS) data at two sites on Vestnesa Ridge, W-Svalbard Margin. Previousgeophysical studies inferred the presence of gas hydrates at shallow depths (up to ~190-195 m below the seafloor) in marine sediments of Vestnesa Ridge. We analyze azimuthal P-wave seismic velocitiesin relation with steeply-dipping near surface faults to studystructural controlson gas hydrate distribution. This uniqueanalysis documentsdirectional changes in seismic velocitiesalong and acrossfaults. P-wavevelocitiesare elevated and reduced by ~0.06-0.08 km/s inazimuths where the raypath plane liesalong the faultplanein the gas hydrate stability zone(GHSZ)and below the base of the GHSZ, respectively. The resulting velocities can be explained with the presence ofgas hydrate-and free gas-filled faults above and below the base of the GHSZ, respectively. Moreover, the occurrence of elevated and reduced (>0.05 km/s) seismic velocities in groups of azimuths bounded by faults,suggestscompartmentalization of gas hydrates and free gas by fault planes. Results from gas hydrate saturation modelling suggest that these observed changes in seismic velocities with azimuth can be due to gas hydrate saturated faults of thickness greater than 20 cm and considerably smaller than300 cm.